Factors that favor or hinder the acquisition of a digital culture in large organizations in Chile - Busco, Carolina; González, Felipe; Aránguiz, Michelle (Frontiers in Psychology, 2023)
The rapid advance of digital technologies in almost all industries has changed the business environment, the competitive dynamics within industries, and customer demand. Organizational culture is often perceived as a valuable strategic asset supporting business transformation and the exploitation of digital technologies. Still, it can also be the source of inertia that impedes change. The research question proposed is What factors favor or hinder the acquisition of digital culture in large organizations in Chile? The aim is to rank factors that promote a digital culture based on the perception of executives using the Delphi method. Research design is empirical, non-probabilistic, cross-sectional, qualitative-quantitative, and exploratory. The expert panel was selected with strategic criteria, considering practical knowledge, up-to-date experience on the subject, and having high decision-making positions in large companies in Chile. To an initial list of 50 possible candidates, 32 experts responded with their willingness to participate and accepted the commitment for the first round, 26 answered the second round, and 23 finally answered the third round of questionnaires between April and May 2022. The main statistics used are media, maximum, minimum, and average range, along with the search for consensus determined by the interquartile range and Kendall’s W concordance coefficient. Results show a high level of agreement on the importance of digital strategy and digital leadership factors when favoring a digital culture in large companies in Chile. However, large companies in Chile must pay attention to the conservative triad of elements that characterize Chilean work culture. The conservative triad contains the belief that changes are exclusively possible when commanded by the strategic apex, a hierarchical work culture that prevents collaborative work, and the rejection of disruptive change. These factors and cultural characteristics will likely hinder any attempt to succeed in a digital transformation plan.